Quantifying dissipation using fluctuating currents - Junang Li (Nature Portfolio, 2019)
The determination of entropy production from experimental data is a challenge but a recently introduced theoretical tool, the thermodynamic uncertainty relation, allows one to infer a lower bound on entropy production. Here the authors provide a critical assessment of the practical implementation of this tool.